An account of short period microseisms recorded during three Indian cyclones (MAUSAM, 1964)
The microseisms in the range of period 4 to 10 secs have been obtained and studied in great detail. The microseisms in the range of period one second or less were studied by the  author previously. It was concluded that the short period microseisms are associated with the passage of cold fronts over or near the station. A few interesting observations of short period microseisms immediately after the passage of cyclonic storms into the land area are presented. The mechanism of generation of these microseisms in relation to the existing theories is discussed.